Mapping Augmented Reality Research for STEM Teaching: Knowledge Evolution and Pedagogical Frontiers - Prelia Dwi Amanah; Rahmatullah Rahmatullah; Gian Aphrodita Emawa; Gunawan Gunawan (Indonesian Journal of Teacher Education, 2022)
This study aims to map the knowledge evolution and pedagogical landscape of augmented reality (AR) research in STEM (Science, Technology, Engineering, and Mathematics) teaching through a descriptive bibliometric analysis approach. Data were obtained from the Dimensions.ai database using the search phrase “Augmented Reality Research for STEM Teaching, Knowledge Evolution and Pedagogical Frontiers” for the 2017–2021 period, yielding 17,152 publications analyzed using VOSviewer software for keyword network visualization, density mapping, and temporal overlay. Results show a fluctuating publication trend that peaked in 2020 (6,110 publications or 35.62%), dominated by book chapters (53.86%), while journal articles contributed only 3.05%. The Information and Computing Sciences category (1,841 publications) and the Human Society field (1,307 publications) were the most productive research areas, while from the SDG perspective, SDG 4: Quality Education (1,648 publications) dominated significantly. Keyword cluster mapping identified interconnections between cognitive themes (mind, brain, thinking), music and culture (music, musicality, culture), and game-based technology (game, virtual, ict), with music and mind as the most central nodes. These findings confirm that AR research in STEM teaching remains fragmented in non-journal formats and requires thematic consolidation toward a more integrated pedagogical framework.